Data-Driven Analysis of the Psychosocial and Behavioral Effects of Social Media Usage in Arabian Gulf Societies - Reem A. Kh. A. Almeshal (International Journal of Computers and Informatics, 2025)
The swift digitization of Gulf societies has changed the ways people communicate and present themselves, but has not yet sufficiently measured its psychosocial impact. This paper introduces a data-driven analysis of behavioral and emotional effects of social-media use in six Arabian Gulf nations: Saudi Arabia, United Arab Emirates, Kuwait, Qatar, Bahrain, and Oman. The analysis incorporates descriptive statistics, correlation matrices, inferential testing, and regression modeling to utilize a structured data set of twenty demographic, behavioral, and psychosocial variables to assess how online activity informs psychological health. Findings indicate that daily hours of use and intensity are positively associated with anxiety and sleep disturbance, while the frequency of peer comparisons and experiences of cyberbullying are associated with anxiety and low self-confidence. Gender and age differences also reveal young females as being more vulnerable to pressures based on appearance and stresses related to social validation. The findings provide a theoretical basis of understanding intersecting behavioral activity, cultural context, and psychosocial ramifications in digitally immersed Gulf communities, as well as underscore the importance of contextualized digital-wellness programming, social-media-literacy education, and policy responses aiming to reduce anxiety related to comparisons and foster good online behavior.